Traditional knowledge system on paddy straw management in North-East India (Indian Journal of Traditional Knowledge (IJTK), 2023)
Burning of paddy straw in the field is a national issue nowadays. Many researches have been taken up for efficient utilization of paddy straw at national and international level. But the use of paddy straw for various applications is known since ancient days. The application of paddy straw varies from region to region. Therefore, an attempt has been made to collect information on the traditional uses of paddy straw and its management in the Northeastern states of India particularly Manipur. The information has been collected through review of literature and interaction with the villagers. The study revealed that the people of this region used paddy straw for different purposes such as thatching, wall construction, cattle feed, animal bedding, fuel, mulching, mushroom cultivation, handicraft products, extraction of substrate from straw ash and preparation of fermented beverages. This traditional knowledge on the utilization of paddy straw can provide an idea for scientific exploration for better and efficient uses in various fields.